2015
DOI: 10.4102/jsava.v86i1.1285
|View full text |Cite
|
Sign up to set email alerts
|

Gastrojejunostomy without partial gastrectomy to manage duodenal stenosis in a dog

Abstract: A nine-year-old female Rottweiler with a history of repeated gastrointestinal ulcerations and three previous surgical interventions related to gastrointestinal ulceration presented with symptoms of anorexia and intermittent vomiting. Benign gastric outflow obstruction was diagnosed in the proximal duodenal area. The initial surgical plan was to perform a pylorectomy with gastroduodenostomy (Billroth I procedure), but owing to substantial scar tissue and adhesions in the area a palliative gastrojejunostomy was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…as stomal ulceration and rapid passage of food [3,4,8]. Although the Billroth II procedure immediately alleviates gastric outflow obstruction and results in clinical improvement during the initial postoperative period, it requires extensive surgery with difficult and delicate surgical techniques [8]. In the present case, neoplasia was extensively involved in the gastric pylorus region and the proximal duodenal region adjacent to major duodenal papilla.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…as stomal ulceration and rapid passage of food [3,4,8]. Although the Billroth II procedure immediately alleviates gastric outflow obstruction and results in clinical improvement during the initial postoperative period, it requires extensive surgery with difficult and delicate surgical techniques [8]. In the present case, neoplasia was extensively involved in the gastric pylorus region and the proximal duodenal region adjacent to major duodenal papilla.…”
Section: Resultsmentioning
confidence: 80%
“…as stomal ulceration and rapid passage of food [3,4,8]. Although the Billroth II procedure immediately alleviates gastric outflow obstruction and results in clinical improvement during the initial postoperative period, it requires extensive surgery with difficult and delicate surgical techniques [8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,6,32 Adequate blood supply is one of the most important factors to successful anastomosis healing and in cases of either shock or hypotension this is significantly decreased and therefore a higher risk for failure and mortality exists. 4,15,25,33 Results of this study identified a trend between hyperlactatemia at presentation and postoperative mortality. Previous reports have also shown a correlation between hyperlactatemia and dog mortality in cases of gastric dilation and volvulus.…”
Section: Discussionmentioning
confidence: 87%
“…Septic shock associated with a gastroduodenal perforation can further compound hypotension and decrease tissue oxygen delivery through the redistribution of the circulatory system to critical organs 4,6,32 . Adequate blood supply is one of the most important factors to successful anastomosis healing and in cases of either shock or hypotension this is significantly decreased and therefore a higher risk for failure and mortality exists 4,15,25,33 …”
Section: Discussionmentioning
confidence: 99%